A secure and enhanced elliptic curve cryptography‐based dynamic authentication scheme using smart card. (27th May 2018) - R, Madhusudhan; Hegde, Manjunath; Memon, Imran
Summary: In remote system security,  2‐factor authentication is one of the security approaches and provides fundamental protection to the system. Recently, numerous 2‐factor authentication schemes are proposed. In 2014, Troung et al proposed an enhanced dynamic authentication scheme using smart card mainly to provide anonymity, secure mutual authentication, and session key security. By the analysis of Troung et al's scheme, we observed that Troung et al' s scheme does not provide user anonymity, perfect forward secrecy, server's secret key security and does not allow the user to choose his/her password. We also identified that Troung et al's scheme is vulnerable to replay attack. To fix these security weaknesses, a robust authentication scheme is proposed and analyzed using the formal verification tool for measuring the robustness. From the observation of computational efficiency of the proposed scheme, we conclude that the scheme is more secure and easy to implement practically. Abstract : We reviewed Troung et al's scheme and identified that the scheme is vulnerable to replay attack, does not provide user anonymity, perfect forward secrecy, server's secret key security, and does not allow the user to choose his/her password. To fix these security weaknesses, a robust authentication scheme is proposed and analyzed using the formal verification tool for measuring the robustness. From the security proofs, we conclude that the proposed scheme is secure and practically implementable.